2013
DOI: 10.1007/s40279-013-0110-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Aerobic Exercise, Resistance Training and Combined Exercise Modalities on Cholesterol and the Lipid Profile: Review, Synthesis and Recommendations

Abstract: There is a direct relationship between chronically elevated cholesterol levels (dyslipidaemia) and coronary heart disease. A reduction in total cholesterol is considered the gold standard in preventative cardiovascular medicine. Exercise has been shown to have positive impacts on the pathogenesis, symptomatology and physical fitness of individuals with dyslipidaemia, and to reduce cholesterol levels. The optimal mode, frequency, intensity and duration of exercise for improvement of cholesterol levels are, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
404
4
23

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 562 publications
(504 citation statements)
references
References 39 publications
36
404
4
23
Order By: Relevance
“…It was demonstrated that exercise especially at low and moderate intensity can enhance lipid utilisation and therefore reduce plasma lipid levels (Mann et al, 2014;Romijn et al, 1993). Our findings showed that a pronounced decrease of TG levels in both exercise groups of J (-17.5%) and OJ (-26.8%).…”
supporting
confidence: 48%
“…It was demonstrated that exercise especially at low and moderate intensity can enhance lipid utilisation and therefore reduce plasma lipid levels (Mann et al, 2014;Romijn et al, 1993). Our findings showed that a pronounced decrease of TG levels in both exercise groups of J (-17.5%) and OJ (-26.8%).…”
supporting
confidence: 48%
“…Regarding specific lipoproteins fractions and TG, we observed beneficial changes to both HDL-C and LDL-C as well as to the TG irrespective of training status. Previous studies have also observed positive (Conceicao et al 2013;Maesta et al 2007;Williams et al 2011), conceivably by mediating LDL-C plasma removal, and lipid oxidation via an increase in lipoprotein lipase (Mann et al 2014). RT also can increase the ability of skeletal muscle to use fat, thereby reducing the levels of plasma lipids (Mann et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have also observed positive (Conceicao et al 2013;Maesta et al 2007;Williams et al 2011), conceivably by mediating LDL-C plasma removal, and lipid oxidation via an increase in lipoprotein lipase (Mann et al 2014). RT also can increase the ability of skeletal muscle to use fat, thereby reducing the levels of plasma lipids (Mann et al 2014). Conversely, other studies found no improvement in lipoprotein after a period of RT (Lera Orsatti et al 2014;Marques et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…In a metaanalysis ET-based CR was associated with significant decreases in total cholesterol level (-14.3 mg/dL; 95% CI: -24.3 to -4.2 mg/dL) and triglycerides (-20.4 mg/dL; 95% CI:-34.5 to -6.2 mg/dL). 87 Controlled trials of ET-based CR have shown that CHD patients benefit from the lowering of total cholesterol and increasing HDL-C. 88 Furthermore, ET as an intervention to facilitate weight loss has been shown to increase insulin sensitivity while decreasing severity of metabolic syndrome and mortality. 89 …”
mentioning
confidence: 99%